Qualitative Analysis of Lipid Composition of Psychrotolerant Serratia Sp. Strain i1p Isolated from Antarctica - Blamey-Alegria, J (Pleiades Publishing, 2025)
Abstract: Serratia sp. strain I1P, a facultative anaerobe of the family Enterobacteriaceae, was recently isolated from Elephant Island, Antarctica. The primary goal of this article was to identify the fatty acid composition and polar lipid profile in the cell membrane as these lipids are known to adapt to the colder temperatures. We extracted total polar lipids from strain I1P cell membrane and characterized the lipid structures of certain isolated fractions by GC-FID chromatography and Tandem Mass spectrometry. We identified several lipid classes, including phosphatidylglycerol, phosphatidylethanolamine, phosphatidic acid, and acyl phosphatidylglycerol. These lipids contained about 46% monounsaturated fatty acids and around 80% short-chain fatty acids (C14−C16). This composition helps the organism maintain the membrane fluidity, especially in colder temperatures, enhancing its ability to survive in such environments. © Pleiades Publishing, Ltd. 2025.